2006
DOI: 10.1897/05-354r.1
|View full text |Cite
|
Sign up to set email alerts
|

Removal and biodegradation of polycyclic aromatic hydrocarbons by Selenastrum capricornutum

Abstract: The removal and degradation of a mixture of polycyclic aromatic hydrocarbons (PAHs), namely phenanthrene (PHE), fluoranthene (FLA), and pyrene (PYR), by a green microalgal species, Selenastrum capricornutum, at different initial cell densities were studied. The PAH removal efficiency increased with the initial cell density, and 96% of PHE, 100% of FLA, and 100% of PYR in the medium were removed by live S. capricornutum at the density of 1 x 10(7) cells/ml in 4 d, whereas less than 50% of PAHs were removed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(72 citation statements)
references
References 35 publications
4
66
0
2
Order By: Relevance
“…Biosorption is a physic-chemical process involved in the sorption of a chemical substance in/on a biological matrix/ surface [16,17]. So far, the biosorption of heavy metal, dyes, and pesticides by biological materials such as bacteria, fungus and algae were extensively reported [1620], but the biosorption of POPs has received considerably less attention.…”
mentioning
confidence: 99%
“…Biosorption is a physic-chemical process involved in the sorption of a chemical substance in/on a biological matrix/ surface [16,17]. So far, the biosorption of heavy metal, dyes, and pesticides by biological materials such as bacteria, fungus and algae were extensively reported [1620], but the biosorption of POPs has received considerably less attention.…”
mentioning
confidence: 99%
“…The molecular weight, water solubility and lipophilicity of the compound would affect the bioaccumulation and degradation by microorganisms. The 4-ring PAHs, Xuoranthene and pyrene, were easier to remove and degrade by Selenastrum capricornutum than phenanthrene, a 3-ring PAH (Chan et al 2013). Similar to microalgae, Potinet et al (2004) reported that two filamentous fungi isolated from PAH-contaminated soil, namely Coniothyrium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Cells cultured in modified SE medium under axenic condition were harvested after 10-12 days [15]. The algal suspension was mixed with heat-dissolved sodium alginate to form 3% algal alginate mixture, dropped into 2.5% calcium chloride solution by a peristaltic pump (Cole-Parmer Instrumental Company Masterflex L/S model 7519-06) to produce immobilized algal beads, each with a diameter of 3 mm.…”
Section: Preparation Of Immobilized Beadsmentioning
confidence: 99%
“…The dissolved alginate matrix was separated from the cells by centrifugation at 2,400 g for 15 min. The PAH concentrations in the medium, in alginate matrix and taken up by cells were extracted by ethyl acetate following the standard method [15], and determined by a Hewlett Packard 5890 gas chromatography (GC) equipped with a flame ionization detector (FID). The fused capillary column (J & W Scientific HP-5MS) was 30 m long with 0.25 mm internal diameter and was coated with methyl silicone of 0.25 µm film thickness.…”
Section: Effects Of Initial Cell Densities Per Bead On Pah Removalmentioning
confidence: 99%